The cyclopropylcarbinyl route to γ-silyl carbocations - Creary, Xavier (Beilstein Journal of Organic Chemistry, 2019)
The mesylate derivative of cis-1-hydroxymethyl-2-trimethylsilylcyclopropane has been prepared, along with a number of related mesylates and triflates with substituents on the 1-position. These substrates all solvolyze in CD3CO2D to give products derived from cyclopropylcarbinyl cations that undergo further rearrangement to give 3-trimethylsilylcyclobutyl cations. These 3-trimethylsilylcyclobutyl cations are stabilized by a long-range rear lobe interaction with the γ-trimethylsilyl group. When the substituent is electron-withdrawing (CF3, CN, or CO2CH3), significant amounts of bicyclobutane products are formed. The bicyclobutanes are a result of γ-trimethylsilyl elimination from the cationic intermediate that has an unusually long calculated Si–C bond. The solvolysis chemistry of mesylate and triflate derivatives of trans-1-hydroxymethyl-2-trimethylsilylcyclopropane and 1-substituted analogs can be quite different since these substrates do not generally lead to 3-trimethylsilylcyclobutyl cations.
Keywords: bicyclobutane; carbocation; cyclopropylcarbinyl; rearrangement; silicon

(untitled) - Merling, G. (Ber. Dtsch. Chem. Ges., 1891)

(untitled) - von E. Doering, W.; Knox, L. H. (J. Am. Chem. Soc., 1954)

(untitled) - Norris, J. F.; Sanders, W. W. (Am. Chem. J., 1901)

(untitled) - Kehrmann, F.; Wentzel, F. (Ber. Dtsch. Chem. Ges., 1901)

(untitled) - Gomberg, M. (Ber. Dtsch. Chem. Ges., 1907)

Carbonium Ions - Freedman, H. H. (Wiley Interscience, 1973)
See for a review and leading references.

(untitled) - Horn, M.; Mayr, H. (J. Phys. Org. Chem., 2012)
See for a review and leading references.

Carbonium Ions - Richey, H. G., Jr (Wiley Interscience, 1972)
See for a leading review.

Carbonium Ions - Wiberg, K. B.; Hess, B. A., Jr; Ashe, A. J., III (Wiley Interscience, 1972)
See for a leading review.

(untitled) - Demjanow, N. J. (Ber. Dtsch. Chem. Ges., 1907)

(untitled) - Roberts, J. D.; Mazur, R. H. (J. Am. Chem. Soc., 1951)

(untitled) - Sneen, R. A.; Lewandowski, K. M.; Taha, I. A. I.; Smith, B. R. (J. Am. Chem. Soc., 1961)

(untitled) - Roberts, J. D.; Mazur, R. H. (J. Am. Chem. Soc., 1951)

(untitled) - Caserio, M. C.; Graham, W. H.; Roberts, J. D. (Tetrahedron, 1960)

(untitled) - von Ragué Schleyer, P.; Majerski, Z. (J. Am. Chem. Soc., 1971)

(untitled) - Olah, G. A.; Reddy, V. P.; Prakash, G. K. S. (Chem. Rev., 1992)

(untitled) - Saunders, M.; Siehl, H. U. (J. Am. Chem. Soc., 1980)

(untitled) - Staral, J. S.; Yavari, I.; Roberts, J. D.; Prakash, G. K. S.; Donovan, D. J.; Olah, G. A. (J. Am. Chem. Soc., 1978)

(untitled) - Koch, W.; Liu, B.; DeFrees, D. J. (J. Am. Chem. Soc., 1988)

(untitled) - Siehl, H.-U. (Adv. Phys. Org. Chem., 2018)

(untitled) - Creary, X. (Chem. Rev., 1991)

(untitled) - Gassman, P. G.; Tidwell, T. T. (Acc. Chem. Res., 1983)

(untitled) - Tidwell, T. T. (Angew. Chem., Int. Ed. Engl., 1984)

Advances in Carbocation Chemistry - Allen, A. D.; Tidwell, T. T. (Jai Press Inc., 1989)

(untitled) - Gassman, P. G.; Talley, J. J. (J. Am. Chem. Soc., 1980)

(untitled) - Gassman, P. G.; Talley, J. J. (J. Am. Chem. Soc., 1980)

(untitled) - Dixon, D. A.; Charlier, P. A.; Gassman, P. G. (J. Am. Chem. Soc., 1980)

(untitled) - Gassman, P. G.; Saito, K. (Tetrahedron Lett., 1981)

(untitled) - Gassman, P. G.; Guggenheim, T. L. (J. Org. Chem., 1982)

(untitled) - Begue, J. P.; Charpentier-Morize, M. (Acc. Chem. Res., 1980)

(untitled) - Creary, X. (Acc. Chem. Res., 1985)

Advances in Carbocation Chemistry - Creary, X. (Jai Press Inc., 1989)

Advances in Carbocation Chemistry - Charpentier-Morize, M.; Begue, J.-P. (Jai Press Inc., 1989)

(untitled) - Creary, X.; Geiger, C. C.; Hilton, K. (J. Am. Chem. Soc., 1983)

(untitled) - Creary, X.; Underiner, T. L. (J. Org. Chem., 1985)

Recent Developments in Carbocation and Onium Ion Chemistry - Siehl, H.-U. (American Chemical Society, 2007)
See for a review and leading references.

The Chemistry of Organosilicon Compounds - Siehl, H.-U.; Müller, T. (John Wiley and Sons)
See for a review and leading references.

(untitled) - Lambert, J. B.; Zhao, Y.; Emblidge, R. W.; Salvador, L. A.; Liu, X.; So, J. H.; Chelius, E. C. (Acc. Chem. Res., 1999)
See for a review and leading references.

(untitled) - Lambert, J. B.; Liu, X. (J. Organomet. Chem., 1996)
See for a review and leading references.

(untitled) - Lambert, J. B. (Tetrahedron, 1990)
See for a review and leading references.

(untitled) - Lambert, J. B.; Chelius, E. C. (J. Am. Chem. Soc., 1990)
See for a review and leading references.

(untitled) - Lambert, J. B.; Wang, G. T.; Finzel, R. B.; Teramura, D. H. (J. Am. Chem. Soc., 1987)
See for a review and leading references.

(untitled) - White, J. M. (Aust. J. Chem., 1995)
See for a review and leading references.

(untitled) - Sommer, L. H.; Bailey, D. L.; Whitmore, F. C. (J. Am. Chem. Soc., 1948)
See for a review and leading references.

(untitled) - Creary, X.; Butchko, M. A. (J. Am. Chem. Soc., 2001)

(untitled) - Creary, X.; Butchko, M. A. (J. Org. Chem., 2001)

(untitled) - Creary, X.; Jiang, Z.; Butchko, M.; McLean, K. (Tetrahedron Lett., 1996)

(untitled) - Creary, X.; Wang, Y.-X. (Tetrahedron Lett., 1989)

(untitled) - Creary, X.; Kochly, E. D. (J. Org. Chem., 2009)

(untitled) - Creary, X.; O'Donnel, B. D.; Vervaeke, M. (J. Org. Chem., 2007)

(untitled) - Siehl, H.-U.; Fulj, M. (Pure Appl. Chem., 1998)

(untitled) - Creary, X.; Kochly, E. D. (J. Org. Chem., 2009)

(untitled) - Creary, X.; Heffron, A. (J. Org. Chem., 2014)

(untitled) - Creary, X.; Heffron, A.; Going, G.; Prado, M. (J. Org. Chem., 2015)

(untitled) - Mercadante, M. A.; Kelly, C. B.; Hamlin, T. A.; Delle Chiaie, K. R.; Drago, M. D.; Duffy, K. K.; Dumas, M. T.; Fager, D. C.; Glod, B. L. C.; Hansen, K. E.; Hill, C. R.; Leising, R. M.; et al. (Chem. Sci., 2014)

(untitled) - Shiner, V. J., Jr; Ensinger, M. W.; Kriz, G. S. (J. Am. Chem. Soc., 1986)

(untitled) - Shiner, V. J., Jr; Ensinger, M. W.; Huffman, J. C. (J. Am. Chem. Soc., 1989)

(untitled) - Grob, C. A.; Gründel, M.; Sawlewicz, P. (Helv. Chim. Acta, 1988)

(untitled) - Adcock, W.; Clark, C. I.; Schiesser, C. H. (J. Am. Chem. Soc., 1996)

(untitled) - Creary, X. (J. Am. Chem. Soc., 2013)

(untitled) - Creary, X. (J. Org. Chem., 2015)

(untitled) - Mascitti, V.; Corey, E. J. (J. Am. Chem. Soc., 2006)

(untitled) - Ohta, H.; Ishizaka, T.; Tatsuzuki, M.; Yoshinaga, M.; Iida, I.; Yamaguchi, T.; Tomishima, Y.; Futaki, N.; Toda, Y.; Saito, S. (Bioorg. Med. Chem., 2008)

(untitled) - Hsee, L. C.; Sardella, D. J. (Magn. Reson. Chem., 1990)

(untitled) - Chen, J.; Reibenspies, J.; Derecskei-Kovacs, A.; Burgess, K. (Chem. Commun., 1999)

(untitled) - Creary, X. (J. Am. Chem. Soc., 1984)

(untitled) - Jansen, M. P.; Koshy, K. M.; Mangru, N. N.; Tidwell, T. T. (J. Am. Chem. Soc., 1981)